ANALYSIS STUDY OF ASHAB AL-KAHF STORY ACCORDING QUR'AN TABARI TAFSIR PERSPECTIVE - Ulil Azmi; Syeih Walid Hamdi Muhammad Abdul Ghaffar; Lismijar Lismijar; Abdul Hadi; M. Isa (Journal of Learning on History and Social Sciences, 2024)
The stories in the Koran are divided into three types, namely stories of prophets, stories related to events that occurred in the past and people whose prophethood was not confirmed and stories related to events that occurred at the time of the Prophet Muhammad. One of the stories in the Qur'an is the story of Ashab Al-Kahf. The mufassir have different views on the story of Ashab Al-Kahf. At-Tabari explained in verse 17 of Surah Al-Kahf about the inclination of the sun from the direction of the cave, the sun rises facing the cave so Allah inclines the sun to the right of the cave so it doesn't hit them. In At-Tabari's Tafsir, there are many differences of opinion on interpretation based on history, as in verse 25 of Surah Al-Kahf, At-Tabari mentions two opinions. First, this verse is the saying of the people of the book. Second, this verse is an explanation from Allah to His Messenger. The difference in interpretation that exists in At-Tabari's Tafsir with the others is influenced by the period of his life among the mufassir, in where at the time of At-Tabari only interpreted verses based on the history in the interpretation without mentioning certain chapters in the verse, while other interpreters who interpreted the verses were arranged according to certain themes so that it was easier to understand one verse as explained in the explanation of the Qur'anic qiraat which was explained based on certain qiraat priests